Racism Towards African-American in Peter Farelly's Green Book (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2020)
The aim of the research was to describe the racial discrimination towards African-American in Green Book, a movie by Peter Farelly. The movie was based on a true story of social life in America during the reign of Jim Crow Laws in 1962. Therefore, the writer used descriptive qualitative method with sociological approach in order to describe the racism act towards colored people in America at that periodical time as depicted in the movie. The research indicated that the historical context of Jim Crow Laws, racial discrimination, the distinction of White and Colored people were reflected in the movie as it is in history. The racial injustice plot was climb up in every states where the concert was held. They went to one region to another further into Deep South. From the first region to the last one, the discrimination kept on increasing from bad to the worst form of racism.